UNRAVELING THE ATOMIC STRUCTURE OF BIOGENIC SILICA: EVIDENCE OF THE STRUCTURAL ASSOCIATION OF AL AND SI IN DIATOM FRUSTULES - Gehlen M.; Beck L.; Calas G.; Flank A.M.; van Bennekom A.J.; Van Beusekom J.E.E. (My University, 2002)
We used X-ray absorption spectroscopy at the Al K-edge to investigate the atomic structure of biogenic silica and to assess the effect of Al on its crystal chemistry. Our study provides the first direct evidence for a structural association of Al and Si in biogenic silica. In samples of cultured diatoms, Al is present exclusively in fourfold coordination. The location and relative intensity of X-ray absorption near-edge structure (XANES) features suggests the structural insertion of tetrahedral Al inside the silica framework synthesized by the organism. In diatom samples collected in the marine environment, Al is present in mixed six- and fourfold coordination. The relative intensity of XANES structures indicates the coexistence of structural Al with a clay component, which most likely reflects sample contamination by adhering mineral particles. Extended X-ray absorption fine structure spectroscopy has been used to get Al-O distances in biogenic silica of cultured diatoms, confirming a tetrahedral coordination. Because of its effect on solubility and reaction kinetics of biogenic silica, the structural association between Al and biogenic silica at the stage of biosynthesis has consequences for the use of sedimentary biogenic silica as an indicator of past environmental conditions.